2015
DOI: 10.1007/s11739-015-1211-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a nutritional education program to improve diet in patients attending a cardiac rehabilitation program: outcomes of a one-year follow-up

Abstract: Dietary habits are widely reported to play a primary role in the occurrence of coronary artery disease (CAD). Cardiac rehabilitation is a multidisciplinary intervention that includes nutritional education. Proper nutrition plays an important role in cardiovascular health outcomes and in decreasing morbidity and mortality of cardiovascular diseases (CVD) as highlighted in the literature. The aim of this study was to assess the efficacy of an educational program to improve the diet of cardiac rehabilitation pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 18 publications
1
22
0
2
Order By: Relevance
“…7 Hence, physical training has been postulated and employed as an important method of rehabilitation in patients suffering from CVDs. 11 However, comprehensive rehabilitation of CVD patients is multifactoral and includes nutritional education followed by changes in dietary habits and supplementation, 12,13 risk factor education, psychological input, and drug therapies to lower low-density lipoprotein (LDL) cholesterol. 14 Exercise training (cardiac rehabilitation [CR]) has been utilized in patients with IHD after myocardial infarction (MI) and other cardiac events, such as percutaneous coronary interventions (PCIs), CABG 15 as well as in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…7 Hence, physical training has been postulated and employed as an important method of rehabilitation in patients suffering from CVDs. 11 However, comprehensive rehabilitation of CVD patients is multifactoral and includes nutritional education followed by changes in dietary habits and supplementation, 12,13 risk factor education, psychological input, and drug therapies to lower low-density lipoprotein (LDL) cholesterol. 14 Exercise training (cardiac rehabilitation [CR]) has been utilized in patients with IHD after myocardial infarction (MI) and other cardiac events, such as percutaneous coronary interventions (PCIs), CABG 15 as well as in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Also Ravazi et al (2014) on a three, twelve and twenty four-month follow up study with 580 participants, observed significant improvements in the decrease of BMI (p < .001 in all the evaluation moments), when evaluating the results of two lifestyle change programs (based on changes in eating habits, physical exercise and stress, amongst other things). [27] In the same way, the study previously referenced, conducted by Luisi et al (2015) demonstrated the important role of individualised educational intervention in the reduction of BMI. [19] Reveles (2015) also presented results showing a significant decrease of BMI (p < .012) and WC (p < .027), in the Portuguese study of 24 individuals with acute coronary syndrome who were followed-up on for six months in an educational nursing intervention program, when compared to the group not submitted to the program.…”
Section: Discussionmentioning
confidence: 64%
“…[27] In the same way, the study previously referenced, conducted by Luisi et al (2015) demonstrated the important role of individualised educational intervention in the reduction of BMI. [19] Reveles (2015) also presented results showing a significant decrease of BMI (p < .012) and WC (p < .027), in the Portuguese study of 24 individuals with acute coronary syndrome who were followed-up on for six months in an educational nursing intervention program, when compared to the group not submitted to the program. [28] The studies presented above show a tendency for significance in the decrease of the anthropometric values, or at least for an improvement of those parameters, which is in accordance with the results that emerge from this study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…(Pimentel et al, 2010). Outro estudo sobre a eficácia do programa de educação nutricional mostrou uma redução significante de peso, IMC e glicemia de jejum nas comparações intra-grupo, mas não entre as comparações entre os grupos, após um ano de acompanhamento (Luisi et al, 2015).…”
Section: Desfechos Antropométricos E Bioquímicosunclassified